Analisis Alokasi Ruang Laut Dalam Rencana Zonasi Wilayah Pesisir dan Pulau-Pulau Kecil (RZWP3K) Provinsi Lampung - Parjito Parjito; Henrie Buchari; Endang Linirin Widiastuti; Samsul Bakri (Jurnal Sumberdaya Akuatik Indopasifik, 2022)
The Zoning Plan for Coastal Zone and Small Islands (RZWP3K) is a plan that determines the direction of resource use for each planning unit accompanied by the determination of the structure and spatial pattern in the coastal planning area. The purpose of this study was to analyze the spatial allocation of marine waters in the Zoning Plan for Coastal Zone and Small Islands in Lampung Province. The method used is the descriptive method. The results of the Zoning Plan analysis for Coastal Areas and Small Islands of Lampung Province are to divide five areas of zoning, namely Public Utilization Areas, Conservation Areas, Certain National Strategic Areas, and Sea Channels, and Special National Strategic Areas. The Public Utilization Area of 1,392,588.32 Ha consists of 7 zones, namely the Tourism Zone, Settlement Zone, Port Zone, Mining Zone, Capture Fisheries Zone, Mariculture Zone, and/or Industrial Zone. The Conservation Area covering an area of 351.645,15 Ha consists of Coastal and Small Islands Conservation Areas/KKP3K (123,080.40 Ha), Marine Conservation Areas/KKP (197,008.75 Ha), and Nature Reserve Areas (31,556.00 Ha). Certain National Strategic Areas covering 73,896.12 Ha, consist of the Outer Small Island of Betuah Island. The National Strategic Area covering 35,194.52 Ha consists of the Lampung Bay Military Training Area and the Sunda Strait Area (KSS). Sea lanes are used for shipping lanes, underwater pipelines/cables, and the migration of marine life. The Zoning Plan for Coastal Zone and Small Islands is an important document for the Provincial Government as the basis for granting a water business permit.